THE QUALITY OF SLEEP IN BRAIN TUMOR PATIENTS - Diansari, Yunni; Handayani, Sri; Mukhlisa; Marisdina, Selly; Syahputri, Rizka Aprillia; Susanty, Tri; Irfannuddin (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
The Quality of Sleep in Brain Tumors Patients. Sleep quality is often compromised in patients with brain tumors. The underlying factors contributing to sleep quality disturbances in this patient population are multifaceted, and investigating these factors remains scarce. Sixty-eight patients with brain tumors, aged ≥ 18 years, were selected consecutively, and data was recorded in the form of sociodemographic characteristics (gender and age), clinical characteristics (clinical manifestations, tumor type, location, comorbid diseases) and therapy characteristics (management and types of drugs). Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data were analyzed bivariate with chi-square and multivariate with logistic regression. Around 45.6% experienced poor sleep quality. Age, gender, systemic malignancies, pain, type of primary brain tumor, tumor location, operation, radiotherapy, and steroid have a significant relationship with sleep quality in patients with brain tumors (p-value <0.05). Multivariate analysis shows that age is the factor that most strongly influences the sleep quality of patients with brain tumors. Age, gender, systemic malignancies, pain, type of primary brain tumor, tumor location, operative treatment, radiotherapy, and steroids influence the quality of sleep in patients with brain tumors, but age has the most decisive influence.